Sex and Gender Differences in Infection and Treatments for Infectious Diseases - Klein, Sabra L.; Roberts, Craig W.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book provides an overview of the underlying sex-based and hormone-based differences in immunity, wound healing and pharmacokinetics, while also exploring how pregnancy affects immunity. The second part of the book shows, for the first time in a single volume, the growing number of infectious diseases for which sex and gender differences are noted, identifies common as well as distinct mechanisms mediating these differences and illustrates how responses to treatments might differ between the sexes. The awareness that males and females differ in their response to specific pathogens as well as to treatments for infectious diseases may yield sex-specific personalized treatments. This book will be of interest to basic scientists and clinicians in the fields of microbiology, immunology and pharmacology. Individuals working in academia, government and industry will also benefit from the information presented.
Section 1 Genes hormones and immunity -- Sex difference in the immune response -- Sex chromosomes and immune function -- Sex and sex hormone mediated differences in wound healing -- Immunology of pregnancy and systemic consequences -- Sex differences in metabolism and pharmacokinetics -- Section 2 Infectious diseases and treatments -- HIV infection and responses to antiretroviral therapies -- Influenza virus infection and vaccination -- Hemorrhagic fever viruses and antiviral therapies -- Tuberculosis diagnosis and treatment -- Respiratory bacterial infection and treatments -- Outcome of bacterial and viral infections and vaccinations in neonates -- Sexually transmitted bacterial infection in women -- Lyme disease diagnosis and treatment -- Protozoan and helminth infections and treatments.
Keywords: Immunology; Infectious diseases; Microbiology; Pharmacology; Immunology; Infectious Diseases; Microbiology; Pharmacology/Toxicology.